Application of different instrumental techniques for adulteration analysis of butter with lard - Ahmad Fadzlillah, Nurrulhidayah (2015)
Determination of food authenticity and detection of adulteration are major concerns not only to consumers, but also to industries and policy makers at all levels of the production process. The major authenticity issues from the food products are the alteration of food ingredients labeling whereby the high value materials are substituted with the cheaper ones without declaring it on the label. Butter is a fairly expensive raw material from an economic point of view, and thus the manufacturers are tempted to look for cheaper substitutes animal fats such as lard. Lard in food are serious matters in view of religious concerns, biological complication and health risk associated with daily intake. In the view of the risk associated with consumption of lard, it is essential to find the most effective, rapid, accurate and sensitive method to identifying the adulterated butter with lard. Therefore, the overall objective of this study is to apply different instrumental techniques for the analysis adulterated butter with lard. In the first phase, butter is prepared through the conventional method, while lard was rendered from adipose tissue of pig using microwave oven. Subsequently, samples of butter and lard were mixed in different concentration (v/v). Each sample admixtures were subjected to analysis of Fourier Transform Infrared (FTIR) spectroscopy, Differential Scanning Calorimetry (DSC), Gas Chromatography Mass Spectrometry (GCMS), High Performance Liquid Chromatography (HPLC) and Nuclear Magnetic Resonance (NMR) spectroscopy. Partial Least Square (PLS) from Fourier Transform Infrared Spectroscopy (FTIR) was successful used to predict lard adulteration in butter with the equation y = 0.998x + 0.0617; was obtained with R2 and RMSEC values were 0.998 and 1.42% (v/v), respectively using 2 PCs. Meanwhile, differential scanning calorimetry (DSC) analysis showed the cooling enthalpy and melting enthalpy for butter, which were -54.06±8.87 J/g and 35.97±4.18 J/g respectively, compared to the cooling and melting enthalpy of lard -10.72 ± 0.89 J/g and 13.95 ± 0.07 J/g, respectively. The cooling enthalpy supports their comparative FA and TAG saturation levels, as butter has a higher saturation FA and TAG, thus leading to a larger cooling enthalpy. In addition, fatty acid (FA) and triacylglycerol (TAG) analysis were also conducted using GCMS and HPLC. Furthermore, the 1H-NMR peak signals at δ2.63 showed a specific characteristic of lard. Heteronuclear multiple bond correlation (HMBC), reconfirmed the assignments of the carbon atom of the palmitoyloleoylinoleic. The results from this study showed the complimentary of various instrumental techniques such as FTIR, DSC, HPLC, GCMS and NMR spectroscopy had adequate sensitivity and selectivity which would be an efficient tool for halal authentication.